Confession as non-criminal prosecution (des)agreement - Lovatto, Aline Correa (2020)
The non-criminal prosecution agreement is a new institute for criminal business law. Incorporated in the Criminal Procedure Code by federal law n. 13,964, provides that the Public Prosecutor's must offer it for cases of infractions that have fulfilled certain legal requirements. However, this institute entered the legal field with several inconsistencies and doubts, one due to the very distorted interpretation that it can cause, the other due to the lack of proper regulation. The confession, which enters as a requirement for the offer of the agreement, for some came in sounding as proof, but in the legal analysis it is nothing more than a pre-procedural act without probative force in a subsequent criminal action, inscribed in a flagrantly unconstitutional rule.